Designing system cost for water pollution plants in mayoralty of Baghdad - محمد بهاء حسين; حميد محمد كريم (Journal of Economics and Administrative Sciences, 2014)
There is an increase in the need for cost accounting in all organizations and from different sectors to provide detailed information to the totals of financial accounting, first and help solve problems associated with inventory and analysis, tabulation and allocation of cost elements II and do the planning process and provide the necessary oversight and help to take the right decisions such as pricing decisions that need to Information cost accounting. And suffer most of the non-governmental organizations from the lack of a cost accounting system provides information on the cost of service in these organizations and the department research sample circle vitality received financial statements of broad interest from various government agencies, the community and even international The cost of access to safe drinking water is one of the vital issues for these entities. The research was to design the system costs a special water purification plants to develop the work of this department and to achieve the goals set forth in the law and meet the requirements of international organizations and the need of the circuit itself. It was in this research compared the cost per square meter of water between that which is calculated in a manner total (by dividing all expenses during the year on the production of water or sold during the same year), however, which was calculated according to the scientific origins of cost accounting. The most important conclusions of the research that he is no longer any reports forcost accounting since the establishment of a special section of it, has not been preparing the trial balance for the year 2013. , And separation of the production costs for marketing costs and administrative kills to reduce the costs of non-value per unit neither of economic nor to the public the beneficiary of these services.That deviates from cost centers to objectively kills Tdid fairer costs and thus does the responsibility of accounting systems, monitoring and evaluation of performance. The most important recommendations, the development of cost accounting system and its reliance on cost allocation activity and identify activities that adds value from those that do not add value and reduce costs and develop the work of the department.